Pelatihan Penggunaan Aplikasi E-RT Berbasis Web pada Rukun Tetangga 006 Perumahan Citra Puri Permata Babadan Ponorogo - Hedi Pandowo; Hamim Tohari; Dian Kusumaningrum; Nova Maulud Widodo; Qimyatussa’adah; Sugiharto (Bulletin of Community Engagement, 2024)
The purpose of community service that we carry out is to facilitate letter-making activities by training Rukun Tetangga administrators to utilize public service applications and manage public information so that residents can keep up with information developments and manage information. The purpose of our community service is to facilitate letter-making activities by training Rukun Tetangga administrators to utilize public service applications and manage public information so that residents can keep up with the development of information and financial management of RT. With the existence of this service application, it is hoped that it can overcome the process time of making letters of introduction and collecting data for residents, both permanent residents and contract residents. The E-RT application is expected to receive full attention from the government and related parties, the existence of standard service standards and infrastructure that meet, the inhibiting factors are public interest, lack of internal support, and lack of infrastructure maintenance, there must be more active information needed, but not just socialization, and training to the public to operate online and transparent funding accountability. A computerized system is needed to facilitate a service and provide information in carrying out a community service process. One of the service activities that is always carried out every day is the service of making all forms of Certificates, Notification Letters intended for residents containing Appeals/information, data collection of underprivileged residents and health information of residents in the Rukun Tetangga area for the current condition is still carried out manually. Manual data processing is not a wrong thing, but it is less effective for processing and calculating large amounts of data, and this can result in data loss. These unwanted mistakes will be very detrimental to the development of citizen data collection